Assessment of pain and structure after an intra-articular injection of adalimumab in osteoarthritis of the knee: A case report. Issue 28 (10th July 2020) - Vasudeva, Abhimanyu; Yadav, Shiv Lal; Nanda, Srishti; Sahu, Samantak
Abstract: Introduction: Tumor necrosis factor alpha (TNF-α) mediated inflammation has been implicated, in knee osteoarthritis, despite being a predominantly degenerative condition. Patient Concerns: A 56-year old female, a case of left knee pain not responding to conventional conservative strategies. Diagnosis: A diagnosis of primary osteoarthritis of the left knee, grade 3 osteoarthritis as per the Kellgren-Lawrence Scale was established. Interventions: She was administered an intra-articular injection of 10 mg of Adalimumab, a commonly used anti-TNF agent. Outcomes: The patient was evaluated at baseline, 1 month, 3 months, and at 6 months. There was a marked improvement in pain intensity (visual analog scale) and quality of life, despite no objective change on the parameters seen on ultrasound of the knee. Conclusion: Injection of adalimumab via the intra-articular route into the knee joint in primary osteoarthritis yields promising results.